Surface Strengthening Behavior of Magnesium Alloy with Laser Thermal Loading under Rapid Cooling - Ge, Y.Q.; Chen, X.; Wang, W.X.; Guo, S. (Проблемы прочности, 2018)
Laser surface strengthening had been performed on an AZ31B magnesium alloy, while the sample was rapidly cooled in liquid nitrogen. Surface strengthening behavior and mechanism were investigated. Because of strengthening mechanisms of fined grains, super solid solution, dislocation and the existence of the amorphous structure, microhardness, wear resistance and fracture toughness of magnesium alloy was greatly improved. Because of the rapid heating and cooling loading of laser, the grains of the strengthening layer were greatly refined, and amorphous structure was formed. And there were more dislocations in the strengthening layer rather than in the substrate. Furthermore, distortion of lattice caused by large numbers of Al element dissolved into α-Mg also increased the resistance to dislocation motion.